Incidence, Risk Factors and Impact on Long-Term Outcome of Postoperative Delirium After Transcatheter Aortic Valve Replacement - Mauri, Victor; Reuter, Kevin; Körber, Maria I.; Wienemann, Hendrik; Lee, Samuel; Eghbalzadeh, Kaveh; Kuhn, Elmar; Baldus, Stephan; Kelm, Malte; Nickenig, Georg; Veulemans, Verena; Jansen, Felix; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background The aim of the present study was to analyze incidence, risk factors, and impact on long-term outcome of postoperative delirium (POD) after transcatheter aortic valve replacement (TAVR). Methods 661 consecutive patients undergoing TAVR were prospectively enrolled from January 2016 to December 2017. POD was assessed regularly during ICU-stay using the CAM-ICU test. Results The incidence of POD was 10.0% (n=66). Patients developing POD were predominantly male (65%), had higher EuroSCORE II (5.4% vs. 3.9%; P=0.041) and were more often considered frail (70% vs. 26%; P<0.001). POD was associated with more periprocedural complications including vascular complications (19.7 vs. 9.4; P=0.017), bleeding (12.1 vs. 5.4%; P=0.0495); stroke (4.5 vs. 0.7%; P=0.025), respiratory failure requiring ventilation (16.7% vs. 1.8%; P<0.001), and pneumonia (34.8% vs. 7.1%; P<0.001). Consequently, patients with POD had significantly longer ICU- (7.9 vs. 3.2 days P<0.001) and hospital-stay (14.9 vs. 9.0 days; P<0.001), and higher in-hospital mortality (6.1 vs. 2.1%; P=0.017). Logistic regression analysis identified male sex (odds ratio (OR) 2.2 (95% confidence interval (CI) 1.2 – 4.0); P=0.012), atrial fibrillation (OR 3.0 (CI 1.6 – 5.6); P<0.001), frailty (OR 4.3 (CI 2.4 – 7.9); P<0.001), pneumonia (OR 4.4 (CI 2.3 – 8.7); P<0.001), stroke (OR 7.0 (CI 1.2 – 41.6); P=0.031), vascular complication (OR 2.9 (CI 1.3 – 6.3); P=0.007), and general anesthesia (OR 2.0 (CI 1.0 – 3.7); P=0.039) as independent predictors of POD. On Cox proportional hazard analysis POD emerged as a significant predictor of 2-year mortality (HR 1.89 (CI 1.06 – 3.36); P=0.030). Conclusion POD is a frequent finding after TAVR and impacts significantly on 2-year survival. Predictors of delirium include not only periprocedural parameters like stroke, pneumonia, vascular complications and general anesthesia but also baseline characteristics as male sex, atrial fibrillation and frailty.